TELEVISED UNDEAD: AN INTERDISCIPLINARY APPROACH TO THE CONCEPTUALIZATION OF VAMPIRES IN CONTEMPORARY TV SHOWS - Corrizzato, Sara; Goracci, Giada (European Scientific Journal, ESJ, 2014)
Drawing on a rich literary tradition, Gothic novels display strange and unreal places such as castles and secret passages where dramatic and amazing events occur and whose effects feeds on an appealing sort of terror. This literary genre expresses an appreciation of extreme passions and emotions and a â€œlonging forâ€ supernatural atmospheres and desolated settings often peopled by monsters, ghosts and vampires. The Gothic fiction has received much fortune throughout the years and, in the contemporary context, it has also been adapted to visual and audiovisual products as a consequence of the peopleâ€™s need to combine the real with the fantastic and transgressions with rules. The word transgression contains in itself a clear reference to the concept of â€œbreaking the boundariesâ€ (trans), going beyond the ordinary life. Seen through this perspective, vampires possess an evocative strength that aptly expresses menâ€™s contemporary quest for â€œlife after deathâ€; indeed, as Bruhm (2002) points out, â€œthe Gothic provides us a guarantee of life even in the face of so much deathâ€ (274). As a matter of fact, in twentieth century films and TV shows vampires and blood-sucking creatures undergo a process of humanization that makes them more â€œaccessibleâ€. This article aims at analyzing the relationship between the Gothic genre and audiovisual products through an interdisciplinary approach that, on the one hand, tracks back the features of this literary genre and accommodates them to present-day necessities and, on the other hand, analyzes the main changes it has encompassed.